Shalom-Based Christian Leadership Development - Marbun, Robinson; Simamora, Anrian; Halawa, Famarudi; ringo, Juspen Siringo-; Toruan, Simon Lumban; Simanjuntak, Wilson (Journal of Comprehensive Science, 2024)
This article discusses the concept of shalom-based Christian leadership, a holistic paradigm that integrates spiritual, social, and economic aspects to build sustainable and positively impactful leadership. In a complex and dynamic world, shalom-based leadership offers a unique approach to creating harmony, peace, and well-being for communities. This article outlines the definition of Christian leadership, the meaning of shalom, and how shalom-based Christian leadership can be developed through the servant, shepherd, and stewardship leadership model. This approach emphasizes the importance of the leader's character, a deep understanding of the harmonious relationship between individuals and groups, and prioritizes the common interest over personal or group interests. The writing method used is qualitative descriptive. The data collection technique used is literature research, which involves searching for and determining books, journals, or other literature relevant to the discussion topic. This approach allows the author to comprehensively understand and explain shalom-based leadership development, producing writing that benefits both the reader and the author.